Single center experience with surgically implanted Melody and Sapien 3 valves in the mitral position in young children - Sicim, Hüseyin; Alaeddine, Mohamad; Velez, Daniel A. (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesMitral valve replacement in young children is a challenging situation due to limited options. In this study, we aimed to present the results of our patients who underwent mitral valve replacement using Melody (Medtronic Inc) and Sapien 3 (Edwards Inc) valves.MethodsWe performed a total of 18 mitral valve replacements at Phoenix Children's between 2017 and 2024. These include 12 Melody and 6 Sapien valves. The median patient age was 42.17 ± 38.9 (1.9–127.2) months and weight was 13.83 ± 9.38 (3.9–43.4) kg, respectively. The indications for implantation were mitral stenosis with or without regurgitation, following an atrioventricular septal defect (AVSD) repair, mitral valve dysplasia, and Shone's complex. Once positioned the valves were expanded using a balloon catheter to achieve the best diameter (16–30 mm).ResultsThe postoperative mean mitral gradient was 6 ± 2.91 (2–12) mmHg. A permanent pacemaker was implanted in one patient after Sapien 3 valve replacement. One patient who received a Sapien valve had to be re-intervened for tamponade in the early post operative period. Mild LVOT obstruction was observed in one patient who underwent Melody valve replacement. One Melody valve was dilated after one year after implantation. At 24 months after implantation, Kaplan–Meier analysis indicated that 80% of Melody valves and 83% of Sapien valves would be expected to be free from reoperation (Log-rank p = 0,56).The hospital stay was 18.72 ± 3.67 days, and no mortality was observed.ConclusionsMelody and Sapien valves contribute to the prognosis of patients as it shortens the operation time, is easily applicable, and provides opportunities such as postoperative redilation. The successful results we obtained show that both valves can be used reliably and effectively and can be an alternative to conventional methods.